«Las cosas soñadas no se cumplen». Il ritratto perduto di Doña Berta fra paradiso e inferno borghese - Coppola, Francesca (Status Quaestionis, 2017)
In Clarín’s novella Doña Berta, a series of objects appear to act as they had their own kind of intelligence that influences the heroine’s behaviour, and without which the story wouldn’t have taken the turn it actually takes along its eleven chapters. This work aims to analyse their narrative function, which is deeply linked to the crucial spatial antithesis “country-city”. This formal opposition is also related to the structure of the novella, working as a background of the main character evolution from passivity to action. As a result of this process, this paper will examine the portraits and, more generally, the domestic objects that are represented in the novella, dividing them in two categories. The first one includes all the objects of the decaying aristocratic world of the family Rondaliego. The second one, instead, refers to those belonging to the bourgeois scene in Madrid during the years of the Restoration, after the age-old conflict between Carlists and Liberals.